Project-based learning e-book with Indonesian local wisdom supporting SDGs to facilitate students’ bioentrepreneurship skills - Alfina Damayanti; Yuni Sri Rahayu; Pramita Yakub (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
The 21st-century competency demands, namely creativity, critical thinking and problem solving, communication, and collaboration. The learning outcomes of the independent curriculum in Indonesia emphasize the importance of students adopting attitudes that support the Sustainable Development Goals (SDGs). Therefore, this research is necessary to produce a valid e-book for facilitating students' bioentrepreneurship skills by incorporating Bojonegoro's local wisdom and supporting SDG 15. The method used in developing the e-book was the 4D model (define, design, develop, and disseminate). Validation which covered content feasibility, presentation feasibility, and language feasibility was carried out by two expert lecturers in the fields of content and instructional media and one biology teacher. Reliability testing was conducted to ensure that the data is trustworthy and consistent. Data analysis was obtained quantitatively and descriptively. The result reveal that content and presentation feasibility are the same, with a score of 3.76 in the very valid category, and the reliability categories are very high at 95% and 93%, respectively. In addition, the language feasibility shows a score of 4, indicating a very valid category with 100% reliability. This result demonstrates that the developed e-book is highly valid for facilitating students' bioentrepreneurship skills.